EXTRAPONTINE MYELINOLYSIS WITH DAMAGE TO THE SUBCRORTIAL NUCLEARS OF THE BRAIN - Светлана Алексеевна Зуева; Валентина Львовна Юрманова; Юрий Михайлович Портнов; Виталий Николаевич Речкин; Владимир Александрович Семенов; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес (Медицина в Кузбассе, 2024)
Extrapontine myelinolysis (EPM) is a rare, severe and difficult to diagnose lesion of the central nervous system (CNS). Studies indicate that the prevalence of this disease ranges from 0.25 to 0.5 % in the general population and 2.5 % in intensive care units. We present a clinical case of EPM in a 63-year-old female patient due to dehydration with early manifestation of behavioral disorders and further development of the clinical picture of parkinsonism.